How to Use Remote Labs for Enhancing E-Learning on PSoCs - Felgueiras, Manuel Carlos (2017)
Electronic teaching is a task that intents to also prepare the student to understand and design analog and digital circuits. However the design flow in those two arenas are quite opposite as result of very different development state and also are the design methodologies, being challeng- ing for both teachers and students. In fact, the electronic design in the digital field is centered in the use of compo- nents based in two kind of circuits (microprocessor and FPGA) using a relatively high level programing/configuring languages. In an opposite way, the analog design is tradi- tionally founded in the use of elementary components (e.g. resistors and capacitors) associated with macroblocks (e.g. operational amplifiers) in order to built-up the wanted mis- sion circuit. However they have just a few analog program- mable components, as the PSoC that is analogically configu- rable in a similar manner that the one already used in the digital domain. The use of this kind of components, howev- er, is not straightforward being necessary to get some con- cepts traditionally not taught in the analog electronic clas- ses. The training using PSoC are then indispensable to veri- fy if the programed analog circuit corresponds to the in- tended one. The current work present an innovative remote lab to sup- port teaching of the PSoC.